A model to understand HIV-related stigma and the psychosocial well-being of children orphaned by AIDS: a theory generative approach - Z. Yassin; C. Erasmus; J. Frantz (Taylor & Francis Group, 2021)
HIV-related stigma has negatively impacted the psychosocial well-being of children who have been orphaned by AIDS-related causes. Response to reducing stigma and ensuring child well-being is hindered by the limited understanding of HIV-related stigma and how it affects the psychosocial well-being of children. Due to the call for a comprehensive understanding of HIV-related stigma, this study aimed to develop a model to understand the manner in which HIV-related stigma affects the psychosocial well-being of children orphaned by AIDS. The study implemented a mixed method, exploratory, sequential design within a theory generative approach that included concept development, statement development, model description, and model evaluation. The developed model indicated that HIV-related stigma is embedded in social interaction and mediated by children orphaned by AIDS response to stigma. HIV-related stigma and maladaptive coping strategies collectively affect several domains of child psychosocial well-being and elevate psychosocial distress. This is the first model to provide a child-centred understanding of HIV-related stigma and its consequences for psychosocial well-being. The model may be used to guide future research and inform the development of appropriate interventions.